2010
DOI: 10.1891/1945-8959.9.3.251
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Self- and Other-Scaffolding on Progression and Variation in Children’s Geometric Analogy Performance: A Microgenetic Research

Abstract: The study investigated geometric analogical reasoning in 8-year-old children by microgenetically examining the (transfer) effects of self- and other-scaffolding and memory capacity on progression and variation in children’s analogy performance. Participants were 54 children, divided over three conditions, and followed for 5 weeks. Children’s initial performances showed a wide strategy repertoire. A number of children profited from repeated self-scaffolding and increased their strategy use considerably. A 20-mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
19
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 39 publications
4
19
1
Order By: Relevance
“…It was not, however, related to the (change) in number of dimensions detected in the task material, or the number and progression of verbal explanations. These findings seem to differ from those of an earlier study by Tunteler and Resing (2010), in which children with a smaller memory span were able to catch 29 up with their peers after training. While the reasons for this discrepancy are unclear, it should be noted that the tasks in the present study were more demanding in terms of cognitive load and most participants, struggled, especially at the initial stage (Halford et al, 2010).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…It was not, however, related to the (change) in number of dimensions detected in the task material, or the number and progression of verbal explanations. These findings seem to differ from those of an earlier study by Tunteler and Resing (2010), in which children with a smaller memory span were able to catch 29 up with their peers after training. While the reasons for this discrepancy are unclear, it should be noted that the tasks in the present study were more demanding in terms of cognitive load and most participants, struggled, especially at the initial stage (Halford et al, 2010).…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings only partially confirm those reported by Tunteler et al (2008) and Tunteler and Resing (2010), who, in their microgenetic studies with classical geometric analogies, found differential progression paths for trained and unguided practice groups, but growth in verbal explanations over time for children in both groups. This may reflect the greater challenge of the items utilized in the present study.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Although children's performance in relation to the construction of transfer tasks was the primary focus of our research, we were also interested in examining if their responses improved as a consequence of repeated practice. Firstly, we examined whether young children, when given opportunities for repeated practice including or not including training, adopted more advanced solving strategies, measured in terms of their a) accuracy, b) use of task-solving components, and c) verbal explanations (e.g., Tunteler & Resing, 2010;Resing et al, 2015). Based on prior research, we hypothesised that performance on these measures would change as a consequence of practice alone and that children in the training condition would outperform children in the unguided practice condition on all measures; we also expected large individual differences (e.g., Resing & Elliott, 2011).…”
mentioning
confidence: 99%